2017
DOI: 10.1155/2017/5071786
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Neuroinflammation to Treat Neuropsychiatric Disorders

Abstract: Neuroinflammation is recognised as one of the potential mechanisms mediating the onset of a broad range of psychiatric disorders and may contribute to nonresponsiveness to current therapies. Both preclinical and clinical studies have indicated that aberrant inflammatory responses can result in altered behavioral responses and cognitive deficits. In this review, we discuss the role of inflammation in the pathogenesis of neuropsychiatric disorders and ask the question if certain genetic copy-number variants (CNV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 204 publications
0
37
0
Order By: Relevance
“…In contrast to TGF-β, a typical inflammatory cytokine, TNF-α did not show much difference in those studies. Neuroinflammation-associated microglial activation is well studied in many neuropsychiatric disorders, especially in major depressive disorder [61]. In our study, elevated serum TNF-α and activated microglia were found in both the LPS and poly I:C groups, but not in the ADX group ( Figure 3).…”
Section: Discussionmentioning
confidence: 48%
“…In contrast to TGF-β, a typical inflammatory cytokine, TNF-α did not show much difference in those studies. Neuroinflammation-associated microglial activation is well studied in many neuropsychiatric disorders, especially in major depressive disorder [61]. In our study, elevated serum TNF-α and activated microglia were found in both the LPS and poly I:C groups, but not in the ADX group ( Figure 3).…”
Section: Discussionmentioning
confidence: 48%
“…Based on clinical and molecular evidence that sterile inflammation of the brain leads to psychotic disorders anti-inflammatory strategies have already been employed in clinical settings [17,46]. The most important anti-inflammatory administered thus far to patients include Minocycline, Celecoxib, Dicloflenac and COX-2 inhibitors [17].…”
Section: New Treatment Strategies Of Sterile Inflammation Of the Brainmentioning
confidence: 99%
“…Based on clinical and molecular evidence that sterile inflammation of the brain leads to psychotic disorders anti-inflammatory strategies have already been employed in clinical settings [17,46]. The most important anti-inflammatory administered thus far to patients include Minocycline, Celecoxib, Dicloflenac and COX-2 inhibitors [17]. These anti-inflammatory drugs have been used alone or in combination with selective serotonin reuptake inhibitors (SSRI) e.g., Escitalopram or tricyclic anti-depressants that increase activity of serotonin in brain -e.g., Nortiptiline.…”
Section: New Treatment Strategies Of Sterile Inflammation Of the Brainmentioning
confidence: 99%
See 2 more Smart Citations